Austrelmis Brown (Coleoptera: Byrrhoidea: Elmidae) from Argentina: five new species - Manzo, Veronica; Archangelsky, Miguel (Zootaxa, 2015)
Material belonging to the genus Austrelmis Brown, from different localities from northwestern Argentina, is studied and described. Five new species are described and illustrated from adults of both sexes: Austrelmis argentinensis sp. nov., A. catamarcensis sp. nov., A. talampayensis sp. nov., A. tafi sp. nov. and A. robustus sp.nov. The new species are compared to other known species of the genus. A comparative table summarizing the most important characters used to identify the argentine species of Austrelmis and a distributional map for Argentina are included.